2016
DOI: 10.1093/jnen/nlw001
|View full text |Cite
|
Sign up to set email alerts
|

Whole Chromosome 7 Gain Predicts Higher Risk of Recurrence in Pediatric Pilocytic Astrocytomas Independently From KIAA1549-BRAF Fusion Status

Abstract: The most frequent genetic alteration identified in pediatric pilocytic astrocytomas and pilomyxoid variant is the KIAA1549-BRAF fusion, which typically results from a 2.0 Mb tandem duplication in chromosome band 7q34. Less frequent abnormalities include fusion genes,BRAF, FGFR, KRAS, and NF1 point mutations, and whole chromosome gains. To correlate genetic alterations with clinical course data, we retrospectively analyzed the tumors with pilocytic and pilomyxoid histology of a cohort of 116 pediatric patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Regardless of whether it is a complete or partial loss of chromosome 10, patients had significantly shorter survival compared to those with no chromosome 10 abnormalities [ 109 ]. Moreover, gain of whole chromosome 7 was associated with a 4.7-fold greater risk of tumor recurrence, even after correcting for surgical status and other genetic changes [ 110 ].…”
Section: Chromosome 7 Gain and Chromosome 10 Lossmentioning
confidence: 99%
“…Regardless of whether it is a complete or partial loss of chromosome 10, patients had significantly shorter survival compared to those with no chromosome 10 abnormalities [ 109 ]. Moreover, gain of whole chromosome 7 was associated with a 4.7-fold greater risk of tumor recurrence, even after correcting for surgical status and other genetic changes [ 110 ].…”
Section: Chromosome 7 Gain and Chromosome 10 Lossmentioning
confidence: 99%
“…Furthermore, a BRAF-TIAA1549 fusion was discovered in pilocytic astrocytoma (more than 70%) ( Fig. 2 ) [ 39 - 43 ]. SMARCB1 (INI1) or SMARCA4 (BRG1) gene mutations or deletions were observed in atypical teratoid/rhabdoid tumors (AT/RT) [ 44 - 46 ], and a NAB2-STAT6 fusion was present in solitary fibrous tumor/hemangiopericytomas [ 47 - 49 ].…”
mentioning
confidence: 99%
“…We found 10 studies that demonstrated detection methods for KIAA1549-BRAF fusion (10,(14)(15)(16)(17)(18)(19)(20)(21)(22). Five of these studies identified the fusion gene variant using direct sequencing, and three studies used only FISH.…”
Section: Discussionmentioning
confidence: 99%